Clinical and pathological features of Henoch-Schonlein purpura nephritis with macrohematuria at the early disease stage - LI Chun-zhen; SUN Chao; ZHANG Dong-feng; LIU Ling; LIU Fu-juan; GE Lan-lan; YUAN Xiao-ying; YIN Mei-na; YANG Yan-jun; CUI Jie-yuan (Linchuang shenzangbing zazhi)
Objective To investigate the clinical and pathological characteristics of Henoch-Schonlein purpura nephritis(HSPN) with macrohematuria at the early diseases stage.Methods The children,who were diagnosed with HSPN ad underwent puncture biopsy in Hebei Province Children’s Hospital Affiliated to Hebei Medical University from January 2016 to June 2019 were analyzed retrospectively.According to the children with or without macrohematuria,they were divided into two groups,and their clinical and pathological characteristics were compared between the two groups.Results A total of 87 children with Henoch Schonlein purpura nephritis were included in the study.Among them,27 children had macrohematuria at the early disease stage,and the other 60 ones were in the control group.There were no statistically significant differences in age,gender and course of disease between the two groups.The levels of serum creatinine,IgA and IgA/C3 in the macrohematuria group were significantly higher than those in the control group,and C3 and serum albumin were significantly lower than those in the control group,with statistically significant differences(P<0.05).There were no statistically significant differences between the two groups in terms of accompanying symptoms(with swelling and pain of limbs,abdominal pain,prodromic infection) and 24-hour urine protein(P>0.05). In terms of pathology,the chronic index of thickening of small vessel walls in the macrohematuria group was significantly lower(P<0.05),the active index of cellular crescents was significantly higher than that in the control group,with statistically significant differences(P<0.05).The C3-positive rate in immunofluorescence assay in the macrohematuria group was significantly higher than that in the control group,with statistically significant differences(P<0.05).There were no statistically significant differences in the proliferation of other mesangial cells and endothelial cells,glomerular segments,glomerular sclerosis,renal tubulointerstitial atrophy,inflammatory cell infiltration and immunofluorescence IgG and IgM deposition(P>0.05).Conclusion The Henoch Schonlein purpura nephritis children with macrohematuria at the early disease stage show significantly decreased serum albumin,increased serum creatinine,and significantly changed immune indexes IgA,C3 and IgA/C3.The biopsy pathology suggests that the chronic index of small vessel wall thickening is lower,the active lesions of cellular crescents and the deposition of complement C3 are more obvious.